Primary tumor cell cultures: сurrent methods of obtaining and subcultivation - I. V. Mezhevova; A. O. Sitkovskaya; O. I. Kit (Южно-Российский онкологический журнал)
Over the past decades, transplantable cell lines have been an affordable model for studying the biology and effect of chemotherapeutic drugs on tumors. However, numerous studies have shown that these cell lines are not heterogeneous enough and cannot reflect the drug resistance of tumors that occurs in some patients. Primary cell line cultures isolated from solid tumors have become widespread in personalized cancer therapy. This review discusses the basic methods for the preparation and cultivation of primary cell lines. A brief description is given of the methods for the disaggregation of tumor material using enzymatic, chemical and mechanical dissociation. The systems of cultivation of primary cell cultures. The selection of an appropriate dissociation method and cultivation is important to preserve the benefits of primary culture in preclinical studies.